2004
DOI: 10.1097/01.shk.0000131579.22409.33
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Regulates Hepatic Inducible Nitric Oxide Synthesis in Vivo

Abstract: The inducible nitric oxide synthase (iNOS) is stimulated to produce large quantities of nitric oxide (NO) by proinflammatory stimuli, hemorrhagic shock, and a variety of cytokines. We have previously shown that cAMP profoundly inhibits hepatocyte iNOS expression in vitro. In this study, we tested whether glucagon, a hormone that increases cAMP in hepatocytes, could regulate hepatic iNOS expression and activity in vivo. Rats were injected intraperitoneally with lipopolysaccharide (LPS, 10 mg/kg) and treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…We cannot exclude the possibility, though, that FK506 regulates pathways other than calcineurin or inhibits other phosphatases. Our current results are consistent with our previous work demonstrating that glucagon and cAMP, compounds known to increase Ca 2+ in hepatocytes, suppress iNOS expression (6,8,13). In hepatocytes, adrenergic agents also increase intracellular Ca 2+ and Collins demonstrated that adrenergic agonists suppress hepatocyte iNOS expression (34).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We cannot exclude the possibility, though, that FK506 regulates pathways other than calcineurin or inhibits other phosphatases. Our current results are consistent with our previous work demonstrating that glucagon and cAMP, compounds known to increase Ca 2+ in hepatocytes, suppress iNOS expression (6,8,13). In hepatocytes, adrenergic agents also increase intracellular Ca 2+ and Collins demonstrated that adrenergic agonists suppress hepatocyte iNOS expression (34).…”
Section: Discussionsupporting
confidence: 94%
“…We have previously demonstrated that hepatocyte iNOS is regulated by cyclic adenosine monophosphate (cAMP) and the cAMP-elevating hormone glucagon (68). Cyclic cAMP and glucagon have profound effects on hepatocyte function by regulating glucose metabolism and expression of phosphoenolpyruvate carboxykinase (PEPCK), the rate-limiting enzyme in hepatic gluconeogenesis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in cAMP, such as occur during times of metabolic stress when circulating glucagon levels are high, protect cultured hepatocytes from apoptosis due to several stimuli including bile acids, Fas, and TNF-␣ (12,21,36,61). In vivo, oral administration of phosphodiesterase inhibitors (18,32) or ␤ 2 -adrenergic agonists (1), agents that increase hepatic cAMP levels, or parenteral administration of glucagon (24) or cell-permeable cAMP analogs (28,57) protect against toxic and ischemic hepatic injury in laboratory animals. Furthermore, it is known that the diseased liver develops dysregulations in cAMP signaling that contribute to increased hepatobiliary damage (15,19,20,27,35).…”
mentioning
confidence: 99%
“…Endogenous mediators that promote Akt activation may therefore downregulate hepatocyte iNOS expression in vitro and in vivo (16,21) and limit iNOS-induced tissue injury in times of stress. Insulin had little effect on p38 in our experiments, and SB203580 had more potent effects on Akt than p38 in these cultures.…”
Section: Discussionmentioning
confidence: 99%